Pacific CRYSTAL Centre for Science, Mathematics, and Technology Literacy: Lessons Learned
IX, 267 p.
Keywords: The University of Victoria Pacific Centre for Scientific and Technological Literacy is one of five Centres for Research into Youth, Science Teaching and Learning (CRYSTAL) funded for 5 years (2005–2010) by the Natural Sciences and Engineering Research Council Canada (NSERC). Pacific CRYSTAL intended to promote scientific, mathematical, and technological literacy for responsible citizenship through research partnerships with university and educational communities. Pacific CRYSTAL’s functional structure consisted of 3 research and development nodes connected to a leadership and administrative node, which was charged with facilitating the activities of 19 projects and 42 principal investigators, partners, and research associates. Node 1, an incubation centre, involved extracurricular authentic science, mathematics, and technology experiences; Node 2, a classroom testing environment, field-tested instructional ideas and strategies to develop evidence-based practices; and Node 3, lighthouse schools, involved systemic change and leadership opportunities that adapted, demonstrated, and disseminated tested ideas, resources, and strategies to a much broader education community and attempted to influence public policy. This book provides descriptions of the target goals, research and development projects, and lessons learned.